Carbon nanotube-mediated high intensity focused ultrasound. Issue 2 (4th June 2021) - Sadeghi-Goughari, Moslem; Jeon, Soo; Kwon, Hyock-Ju
Abstract: High intensity focused ultrasound (HIFU) is emerging as a novel therapeutic technique for cancer treatment through a hyperthermal mechanism using ultrasound. However, collateral thermal damages to healthy tissue and skin burns due to the use of high levels of ultrasonic energy during HIFU treatment remain major challenges to clinical application. The main objective of the current study is to evaluate the potential of carbon nanotubes (CNTs) as effective absorption-enhancing agents for HIFU to mediate the heating process at low ultrasonic power levels, and consequently upgrade hyperthermal therapeutic effects of HIFU. An experimental study using in vitro tissue phantoms was conducted to assess the effects of CNTs on HIFU's heating mechanism. Detailed information was extracted from the experiments for thermal analysis, including rate of absorbed energy density and temperature rise profile at the focal region. Parametric studies were carried out, revealing the effects of ultrasound parameters (ultrasonic power and driving frequency) on the performance of CNTs in various concentrations. The results indicated that CNTs significantly enhanced the thermal effect of HIFU by elevating energy absorption rate and consequential temperature rise. Moreover, it was demonstrated that an increase in ultrasonic power and driving frequency could lead to a better performance of CNTs during HIFU ablation procedures; the effects of CNTs could be further enhanced by increasing their volume concentration inside the medium.